Computing via natural erosion of sandstone. Issue 6 (2nd November 2018) - Safonov, Alexander A.
Abstract: Logical gates are constructed based on a method of numerical modeling of natural erosion of sandstone. Values of logical variables are determined by the presence of sandstone. The presence of sandstone corresponds to the logical value of True, whereas the absence of material corresponds to the False value. Logical functions are computed through the formation of sandstone structures at action of natural erosion where loading conditions are specified. AND and XOR gates and a one-bit binary half-adder are implemented. Abstract : One-bit half-adder implementation.